2018
DOI: 10.1016/j.cmet.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Translating In Vitro T Cell Metabolic Findings to In Vivo Tumor Models of Nutrient Competition

Abstract: Reductionist in vitro T cell assays have identified metabolic pathways critical for T cell function within the tumor microenvironment. We discuss the challenges of testing these concepts using in vivo tumor models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Intriguingly, depletion of myeloid cells capable of degrading arginine and tryptophan from PDAC tumors resulted in increased T cell infiltration, proliferation, and activation in PDAC tumors (Bayne et al, 2012; Stromnes et al, 2014; Zhang et al, 2017). Future studies determining how T cell metabolism and function is impacted by tumor nutrient levels could yield insight into how tumors suppress immune rejection (Ecker and Riley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, depletion of myeloid cells capable of degrading arginine and tryptophan from PDAC tumors resulted in increased T cell infiltration, proliferation, and activation in PDAC tumors (Bayne et al, 2012; Stromnes et al, 2014; Zhang et al, 2017). Future studies determining how T cell metabolism and function is impacted by tumor nutrient levels could yield insight into how tumors suppress immune rejection (Ecker and Riley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With the gene expression profiles of single cells from tumors, we were able to identify metabolic features that distinguish subpopulations of immune and stromal cells. This approach has the advantage of providing a direct snapshot of the metabolic landscape of tumors and their microenvironment consisting of numerous known and unknown types of cells whose metabolism is greatly influenced by the interactions between them and the shortage of nutrients in the tumor microenvironment 11,58,59 . We found that some non-malignant cell subpopulations, Ths and Tregs for instance, adopt metabolic phenotypes distinct from what they show in ex vivo culture conditions 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports indicate that the metabolic rewiring of tumors interferes with antitumor immunity in many ways (reviewed by ref. 37). On one hand, tumor-derived metabolites, such as lactate or adenosine, influence the immune response.…”
Section: Discussionmentioning
confidence: 99%